STUDI EKOLOGI TEMPAT BERKEMBANGBIAK NYAMUK Aedes sp DI KOTA METRO SEBAGAI SUMBER BELAJAR BIOLOGI MATERI POKOK INSEKTA - Suharno Zen (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
In Indonesia, dengue disease is becoming one of the health problems often occurs Extraordinary Events (KLB) in adults and even in children. It is closely related to the change of seasons, migration, as well as the places for mosquitoes to breed. This method is a survey / field observations. The data collection is done by sampling mosquito larvae inside and outside the home on each of 10 homes inspected every district in Metro Centre, Metro West, Metro North and Metro South. In practice, a survey carried out by using the method of single larvae is done by taking a single larva in every places that hold water found there to be further larvae further identification of the type of larvae. Based on the results of the study, obtained the following conclusions: Container / used as breeding places of Aedes sp in Metro City in 2013, are etub, old tires, bottles, coconut shells, buckets, cups, flower pots, bowls scars, brown skin, cans, drums, trash cans and fish ponds. The number of mosquito larvae Aedes sp found as many as 283 tail consisting of species Aedes aegypti and Aedes albopictus. The need for further research to determine the value of Numbers Free Flick (ABJ), House Index (HI), Container Index (CI), Breteau Index (BI) as well as education / socialization programs 3M plus follow up every 3 months to the public.Kata kunci: Extraordinary Events, Numbers Free Flick (ABJ), House Index (HI), Container Index (CI), Breteau Index (BI)